Tenere un cielo per cinque anni (Materiali di Estetica. Terza serie, 2022)
The article is dedicated to the great work of Ernesto Treccani for the house in via Porta in Milan, headquarters of Fondazione Corrente, conceived in the form of a sculpted and painted ceramic wall, consisting of over two thousand tiles, all different from each other. In this monumental work, Treccani shows a language that updates the line of post-impressionist Lombard tonalism according to the ways of a painting of matter and gesture
Keywords: Ernesto Treccani; Ceramic; Sculpture; Architecture